1985
DOI: 10.1007/bf01913309
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and thermoanalytical characterization of standard substances for the identification of reaction products on iron electrodes

Abstract: OFThe in situ spectroscopic investigation of electrochemical, and especially corrosion processes in iron requires well-characterized reference substances. It has been found that the application of spectroscopic methods alone is not sufficient for the detection of impurities in certain phases. Thermoanalytical methods have therefore additionally been used to detect impurities and to optimize the preparation methods. Infrared and Raman spectra and thermoanalytical data on aFeOOH, fl-FeOOH, ~,-FeOOH, &FeOOH and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 18 publications
4
46
0
Order By: Relevance
“…Raman spectra on various goethite-rich areas are shown in Figures 2a to 2d. The spectra show broad bands at 298 and 395 cm -1 suggesting poorly or microcrystalline goethite, and sharp peaks, indicative of more crystalline goethite, at 240,298,395,478,549,687,1001,1116 and 1302 cm -1 (Nauer et al 1985, Dünnwald & Otto 1989. The width and the slight shift of some of the Raman peaks may also be attributed to sulfur.…”
Section: Morphological and Mineralogical Characteristics Of The Two Smentioning
confidence: 93%
“…Raman spectra on various goethite-rich areas are shown in Figures 2a to 2d. The spectra show broad bands at 298 and 395 cm -1 suggesting poorly or microcrystalline goethite, and sharp peaks, indicative of more crystalline goethite, at 240,298,395,478,549,687,1001,1116 and 1302 cm -1 (Nauer et al 1985, Dünnwald & Otto 1989. The width and the slight shift of some of the Raman peaks may also be attributed to sulfur.…”
Section: Morphological and Mineralogical Characteristics Of The Two Smentioning
confidence: 93%
“…This spectrum is very similar to the maghemite spectra shown by De Faria et al 21 and Boucherit et al 17 The broad band at around 700 cm 1 can also be observed on other iron components. In this region, it can be assigned to υ-FeOOH 19,21,27,28 or to ferrihydrite. 11,29 These phases were synthesised following the procedure of Schwertmann and Cornell 26 and analysed by Raman spectroscopy (Fig.…”
Section: Identification Of Iron Corrosion Products By Raman Micro-spementioning
confidence: 99%
“…Keiser et al 27 present a spectrum with the main peak at 678 cm 1 , Nauer et al 28 at 663 cm 1 and Boucherit et al 19 at 655 cm 1 . Our spectrum is very similar to the one given by De Faria et al, 21 which gives two peaks, the one at 680 cm 1 being the most intense and that at 400 cm 1 being the second.…”
Section: Identification Of Iron Corrosion Products By Raman Micro-spementioning
confidence: 99%
“…The positions of the important absorption bands for the various iron containing phases are summarized in Table 1 [9]- [15]. This table is modeled after the work by Nauer et al [9] that tabulated the peak positions of goethite (δ-FeOOH), akaganéite (δ-FeOOH), lepidocrocite (δ-FeOOH), feroxyhite (δ-FeOOH), and bernalite (Fe(OH) 3 ). These authors also used the following assignments for IR absorbances: 1) 3600 to ca.…”
Section: Product Characterizationmentioning
confidence: 99%